A Qualitative Study of Employees’ Motivation Factors on Organization : A Case Study from a Company in Indonesia - Setiawan, Danu Ade (Faculty of Economics and Business, Hasanuddin University, 2020)
Due to the vital function of employees in the organizations that leads to both financial and non-financial performance, it is necessary for management to increase the motivation of their employees. Plenty of researches were conducted in past decades in the topic of employees motivation with the purpose of finding the factors that affect the employees’ motivation significantly. This paper examined employees’ motivation factors in one of Indonesia’s state owned company. Through qualitative approaches, in-depth interviews were conducted to eight active employees with a focus on four predetermined motivation factors that are salary, growth opportunity, work-life balance, and reward/recognition. The result found that all of the predetermined factors has an influence on the employees’ motivation in order to perform well in the company. Furthermore, the findings also discover some conditions required to be improved regarding specific employees characteristic such as supervisory level position. In the end, this paper is expected to generate some possible recommendations for organization in order to maintain and increase employees’ motivation.